Corporate Social Responsibility: Profitabilitas Dan Risiko Litigasi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia(BEI - Orolaleng, Novitaria Dae; Erawati, Teguh (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study adopts a quantitative approach model where the population includes manufacturing companies listed on the Indonesia Stock Exchange during the period 2019 to 2022. The sample was selected by purposive sampling which included 200 manufacturing companies. As for this study using secondary data taken from www.idx.co.id. To analyze the data, multiple regression methods, coefficient of determination analysis, and classical assumption testing were used. The results showed that: 1) profitability has a positive effect on CSR, 2) litigation risk also has a positive effect on CSR